Simultaneous Photocatalytic Reduction of Cr(VI) and Oxidation of Benzoic Acid in Aqueous N-F-Codoped TiO2 Suspensions: Optimization and Modeling Using the Response Surface Methodology - Maria Antonopoulou; Aris Giannakas; Ioannis Konstantinou (International Journal of Photoenergy)
The simultaneous photocatalytic reduction of Cr(VI) and oxidation of benzoic acid (BA) in aqueous suspensions using N-F-codoped TiO2 and simulated solar irradiation were investigated in the present study. Chemometric optimization tools such as response surface methodology (RSM) and experimental design were used to model and optimize selected operational parameters of the simultaneous photocatalytic reduction of Cr(VI) and oxidation of BA. RSM was developed by considering a central composite design with three input variables, that are, N-F-codoped TiO2 mass, ratio of Cr/BA, and pH. The removal of Cr(VI) and BA in binary systems, containing both Cr(VI) and BA, showed a synergistic photocatalytic decontamination as BA significantly facilitated Cr(VI) reduction, whereas Cr(VI) accelerated also BA degradation. Due to the anionic-type adsorption onto TiO2 and its acid-catalyzed photocatalytic reduction, the removal of Cr(VI) decreased with increasing pH, while the degradation of BA followed also the same trend. Under the optimum conditions (N-F-TiO2) = 600 mg L−1, ratio of Cr(VI)/BA = 5, pH = 4, the removal for both Cr and BA followed a pseudo first-order kinetic model. It was found that the selected variables have significant effect both on Cr(VI) removal and BA degradation efficiency. The results revealed the feasibility and the effectiveness of using N-F-codoped TiO2 as photocatalyst for simultaneous decontamination of Cr(VI) and organic pollutants such as BA due to the appropriate oxidation and reduction ability of the photogenerated h+VB-e−CB pairs.